The development and manufacture of a composite mobility aid for a Paralympic table tennis player - Pickup, R. (The Plymouth Student Scientist, 2021)
Table Tennis is the third largest ParalympicSport with competitors competing from over a hundred countries. David Wetherill is a three-time Paralympian who will be competing in the Tokyo 2020 Paralympic Games and currently competes with a standard crutch. This paperis based around improving the crutch for Mr Wetherill using the research to advise on how crutches can be improved for long term users, providing them a better quality of life. For Mr Wetherill the goals were to create a composite mobility aid that met all the requirements laid out by the athlete and using current research in different mobility aids, advancements in materials and manufacture techniques. Full CAD models were created using both Solidworks and ANSYS software`s showing the smallest failure of 875N is considered satisfactory. With results validated using first principal calculations and coupon testing. A final design was created and will be manufacture in the fall of 2020, to be used by Mr Wetherill at the Tokyo 2020 Paralympic Games. Applying the current research into crutches and understanding current issues long term users face, design changes have been advised using the advancements in manufacture techniques or materials, for example 3D printing and composite materials to improve the quality of life of long-term crutch users.